Analysis of Maternal Mortality Due to Hypertension in Pregnancy in West Bandung - Karwati Karwati; Wiryawan Permadi; Dewi M.D. Herawati (Health Notions, 2019)
Hypertension in pregnancy is one of causes in maternal mortality in West Bandung District in 2017 and there are 11 mothers (39.28%) of 28 mortality cases, which is in the highest rank. Moreover, this research aimed at analyzing maternal mortality due to hypertension in pregnancy in West Bandung District. This research was qualitative research by utilizing grounded theory approach with constructivism paradigm. Sample of this research was the closest family and health personnels who knew the cronology of maternal mortality and there were 21 people from 8 mortality cases. The sample collection utilized purposive sampling technique. Meanwhile, the instruments of this research were researchers, interview guidance, stationery, and voice recorder. Validity test utilized triangulation technique. Technique of data collection was by in depth interview and the analysis process were by transcription, reduction, coding, categorization, and theme. The result of this research was known that factors, which had contribution against maternal mortality, was such as poor access of health service and it was caused by several things: PONED function that had not been optimal in handling hypertension in pregnancy, poor quality of health service, guidance in handling hypertension in pregnancy that had not been optimal, less optimal information from health service, health personnel’s poor knowledge about hypertension in pregnancy, and delay in referring to hospital. The next factor was unhealthy living behavior, such as mother who had risk of hypertension in pregnancy did not use long-term contraception, underwent quite high failure level in the use of long-term contraception, the mother was a missing patient from the referral, and not sensitive against emergency situation. Besides that, unknown or unexpected factors also became contribution against mortality, such as unclear demographic status; undesirable pregnancy; assuming that dying in pregnancy, having birth, and in postpartum period was martyred. In conclusion, factors that contributed against maternal mortality due to hypertension in pregnancy in West Bandung District were access of health service, healthy living behavior, and unknown even unexpected factors. However, the factors that really impacted against maternal mortality were access of health service and healthy living behavior. Keywords: Maternal mortality, Hypertension in pregnancy